Tindak Tutur Ilokusi Pada Interaksi Jual Beli di Pasar Rejowinangun, Kota Magelang - Afiq, Muhammad Nur; Herpindo; Shalima, Irsyadi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This research aims to describe the form and function of illocutionary speech acts of buying and selling interactions of Rejowinangun Market, Magelang City. To achieve the purpose, this research uses pragmatics approach with qualitative descriptive method. The data is in the form of speech or utterances that occur naturally in transactions between sellers and buyers. The data collection techniques used were (1) tapping and (2) recording. Data analysis was conducted through data reduction, presentation, and interactive conclusion. The results showed that the buying and selling interaction at Rejowinangun Market, five forms of illocutionary speech acts were found, assertive, directive, commissive, expressive, and declarative. Assertive are used to state factual information, directive is used to influence speech partners, commissive contains promises or commitments of speakers, expressive reflects emotional attitudes, and declarative changes social conditions directly